Administrative Will to Power: Articulating the Goals of Antitrust and Proposing Therefor a Regulatory Framework - Marella, Jose Maria L. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
I. Beyond Economic Efficiency & Consumer Welfare; II. The Old Gods: Economic Efficiency and Consumer Welfare; III. The Old Gods are Dead: Articulating the Other Goals of Antitrust; Overcoming: A Framework for Regulation; V. Conclusion: Will to Power.
Keywords: Antitrust law; Economic policy; Competition - Law